(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The experiment was carried out at Agriculture Research Farm of Rama University, Mandhana, Kanpur, U.P, India, during October 2021-2022 to investigate the effect of integrated nutrient management on plant growth, & yield parameter of strawberry (Fragaria x ananassa Duch.) var. Chandlar” eight treatments viz., T1(Control), T2(100% RDF N: P: K @ 6:10:6 g/plant), T3(100% RDF + Azotobacter @ 2g/plant), T4(100% RDF + Azospirillum @ 2g/plant), T5(50% RDF + Azotobacter @ 2g/plant + topdressing of 50% each of P and K), T6(50% RDF + Azospirillum @ 2g/plant + topdressing of 50% each of P and K), T7(50% RDF + Azotobacter @ 2g/plant + PSB @2g/plant + topdressing of 50% K) and T8(50% RDF + Azospirillum @ 2g/plant + PSB @2g/plant + topdressing of 50% K) along with their combinations, replicated thrice in a Randomized Block Design. In strawberry use the application of fertilizer with bio-fertilizer like Azotobacter and Azospirillum hasten early flowering along with the expanded duration of blossoming, harvesting by increasing the growth, yield and quality of strawberry. The integrated nutrient management maximized plant height (cm), number of leaves per plant, plant area (cm2), number of runners per plant, number of flowers per plant, number of berries per plant, fruit weight (g), fruit length (mm), fruit diameter (mm), fruit yield/plot (kg).